Prevalence of inducible clindamycin resistance in methicillin-resistant Staphylococcus aureus: the first study in Jordan - Jarajreh, Dua’a; Aqel, Amin; Alzoubi, Hamed; Al-Zereini, Wael (The Journal of Infection in Developing Countries, 2017)
Introduction: A high rate of infections with methicillin-resistant Staphylococcus aureus (MRSA) has been documented, in both hospital- (HA-MRSA) and community-acquired (CA-MRSA) diseases in Jordan. Erythromycin and clindamycin are considered treatments of choice. However, resistance to erythromycin with false susceptibility to clindamycin in vitro may lead to therapeutic failure. Hence, it is mandatory to study the prevalence of inducible resistance to macrolide-lincosamide-streptogramin B (iMLSB) antibiotics conferred by erm genes in those bacteria. Methodology: S. aureus isolates were identified morphologically and biochemically, and MRSA were appraised using standard procedures. Induction in resistance to MLSB antibiotics among MRSA isolates was detected phenotypically using the D-test, and the presence of erm genes was revealed by polymerase chain reaction (PCR). Results: Of 126 collected Staphylococcus isolates, 71 (56.3%) isolates were S. aureus, of which 55 (77.5%) were MRSA. A total of 43 (78.2%) MRSA-discordant isolates were resistant to erythromycin, of which 33 (76.7%) exhibited the iMLSB (D-test positive), 2 (4.7%) the MSB (D-test negative), and 8 (18.6%) the constitutive resistant (cMLSB) phenotypes. Induction of clindamycin resistance was 1.6 times greater in CA-MRSA than in HA-MRSA. Furthermore, ermA and ermC were significantly prevalent in HA-MRSA and CA-MRSA, respectively. Conclusions: Continuous surveillance of the MLSB resistance is important and required before the prescription of clindamycin to treat MRSA infections.